Implementation of Qris Transaction Fee Charges On Micro Business Actors in Samarinda City - FH UNMUL, Nur Hidayanti; FH UNMUL, M. Fauzi; FH UNMUL, Febri Noor Hediati (Universitas Negeri Semarang, 2024)
The significant advancement of technology has encouraged people to develop businesses through the Internet. To support the times, a technology-based payment method was formed technology. One of them is the QRIS payment method which is widely used today. QRIS is the latest breakthrough launched by Bank Indonesia in collaboration with the Payment System Association of Indonesia. QRIS is a standardization of electronic payments based on standardization and aims to unify non-cash payments based on QR codes in Indonesia. This research uses a social legal approach that focuses on micro-business actors and the implementation of Bank Indonesia regulations. Primary data sources are the results of interviews with micro business actors in Samarinda City and the results of interviews with Bank Indonesia Representatives. Samarinda City and the results of interviews with Bank Indonesia Representative of East Kalimantan. Secondary data used is Bank Indonesia Regulation No. 23/6/2021 concerning payment service providers, Consumer protection law, books, articles, and journals. Tertiary data used are Indonesian dictionaries and legal dictionaries. Implementation of QRIS transaction fees on micro-business actors Micro businesses in Samarinda City has not run optimally by Bank Indonesia regulations. Minimal profit is one of the reasons for micro-business actors not implement BI regulation. Thus, in terms of legal effectiveness according to Soejono Soekanto then the charging of QRIS transaction fees to micro businesses is not effective